ANALISA RASIO SOLVABILITAS LAPORAN KEUANGAN (STUDI KASUS : PT CEMERLANG JAKARTA) - Fahmi Kamal (Universitas Bina Sarana Informatika, 2015)
Each company has financial statement ratios, including solvency ratios. The financial statements required by a company to measure and assess the performance of the company because in it there is important information about the company's earnings and financial position of the company's capabilities. The financial statements can be analyzed to see the condition of the company. Type of financial statements analysis varies according to the interests of the parties will conduct the analysis. One way to analyze financial reports by performing the analysis of the solvency ratio. The purpose of this study was to determine the level of solvency PT Cemerlang Jakarta. Solvency ratio analysis will provide a better understanding of the financial condition analyzed. Indicators used in the solvency ratio analysis consists of: Total Debt to Total Assets Ratio, Debt to Equity Ratio / Equity Ratio Debt, Long Term Debt to Equity Ratio. From the analysis of financial statements in 2011 and 2012 Jakarta PT Cemerlang changes, where in 2011 the financial statements of the company in 2012 while insolvable financial statements solvable. Analysis of the financial statements required to monitor the progress of the company and to anticipate the various possibilities that will occur at the company, so that the management company can make decisions quickly and accurately. Keywords: Solvency Ratio, Financial Statements